Lenovo Group Ltd. : Achieving Competitive Advantages for its Hardware Business in Emerging Markets by Developing a Sustainable Business Model for its Software and Peripherals Business-The Malaysia Scenario. - Chin, Andrew Beng Huat (2010)
From a humble beginning in late 1984, not much dufferent from how Hewlett-Packard Co. and Apple Inc. began from their family home garages, Lenovo Group Ltd., previously known as Legend Group Ltd. until 2003, is today the pride and joy in home country the People's Republic of China. By 1998, Lenovo had shipped its millionth personal computer (PC), and then Intel chairman, Andy Grove took the Legend PC back for Intel's museum collection. In 2003, Lenovo built and launched its second supercomputer the Legend DeepComp 6800, which was ranked fourteenth in performance in the 2003 Top 500 list of the world's fastest supercomputers. For the past eight years since 2002, based on International Data Corporation (IDC) data, Lenovo is the numero uno manufacturer and supplier of PCs in the Asia Pacific, ahead of the ranked competitor Hewlett-Packard by a sizable volume. For example, for the 24 months period from July 2008 to June 2010, Lenovo shipped 33.4 million units in Asia Pacific, outselling Hewlett-Packard by 7.9 million units.